Sex steroid receptor proteins in foetal, adult and malignant human liver tissue. - Iqbal, M. J. (Nature Publishing Group, 1983)
Sex steroid receptor proteins were studied in human normal liver and hepatocellular carcinoma (HCC). Oestrogen receptor (ER) was detected in nucleosol and cytosol of 4 normal adult and 5 malignant liver specimens and in the cytosol of 6 foetal liver samples. Levels were 27.6-500 fmol mg-1 soluble protein in normal adults (Kd 1.48 X 10(-8) -1.12 X 10(-10) mol 1(-1) ), 45-290 fmol mg-1 in malignant liver tissue (Kd 3.26 X 10(-9) -3.64 X 10(-10) mol 1(-1] and a mean of 93 fmol mg-1 in foetal tissue (Kd 1.55 X 10(-9) mol 1(-1]. Androgen receptors (AR) were found only in cytosol and nucleosol of HCC (23-370 fmol mg-1) and in cytosol from foetal liver (29 fmol mg-1) with Kd from 2.90 X 10(-9) to 3.734 X 10(-10) mol 1(-1]. AR was distinguished from sex hormone binding globulin, which was also present in all cytosol samples, by the former's ability to selectively bind to methyltrienolone and the latter's absence from nucleosol. These findings provide further support for suggestions that oestrogen-related hepatic functions in man may be mediated by receptors and raise the possibility that hepatocellular carcinoma may be androgen dependent.